The work environment and the perception of the institutional image of the Luis Vargas Torres Technical University - Ecuador - Guaman-Chavez, Ramiro Enrique; Vélez, Eng. Tito Gimmy Jácome; Fernanda, Bravo Bravo, Idilia; Cuadros, Ing. Yadira Natalia Vergara (Journal of Posthumanism, 2025)
The work environment is based on work motivations, regulates institutional and organizational life, promotes a type of behavior and relationships between workers, it fulfills the function of nexus between its actors; two years ago where the labor conflict within the university campus has multiplied, this makes the dimension of the work and organizational climate disjointed, good compliance with institutional policies is not possible and it makes it impossible to comply with the processes in relation to teaching and the deficiency in the institutional mission, where the work environment is absent and deteriorated. The present research aims to analyze how the work environment is related to the perception of the image, a quantitative approach with correlation, descriptive, explanatory and non-experimental design was used, these methods will be focused on revealing the cause of the events, event and phenomena that occur in the educational institution, which affects the work environment.The statistical technique used was the Pearson correlation coefficient and a Trux index survey, it was applied to teaching staff, service, administrative staff and students; After obtaining the results, it is determined that one thing affects the other, that is, there is a positive and statistically significant correlation between them; Due to the nature of the study, it is not possible to establish causal relationships, however, it is feasible to affirm that the better the work environment, the greater the degree of perception of institutional satisfaction of the university campus.